Analisis Semiotika dan Desain Komunikasi Visual dalam Video Dokumenter ” The Painting of Life Vincent Van Gogh” - Anak Agung Gede Daniartha (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study analyzes visual representation in a documentary video about Vincent van Gogh through the lens of deconstructionist semiotics and visual communication design principles, with particular focus on the application of Dadaist style and experimental typography. The research is motivated by the crucial role of design consistency in effectively conveying symbolic messages through visual media. Employing qualitative methods, the study examines characteristic Dadaist elements such as collage, random image fragments, and unconventional typography in expressing a narrative of rebellion. Findings indicate that the opening bumper successfully creates a